Screening of barley germplasm and released cultivars against stripe disease (Drechslera graminea) under artifical inoculation condition - Kumar, Virendra; Shekhawat, P. S.; Kanwar, Harshraj (Journal of Cereal Research, 2019)
Barley (Hordeum vulgare L.) is the fourth largest cerealcrop in the world with a share of 7% of the global cerealproduction (Pal et al., 2012). It is mainly grown as a rabiseason crop in different temperate regions of the worldincluding India. Barley is used as a feed for animals,malt for industrial uses and for human food. At present,Barley is subjected to various fungal, bacterial, viraland noninfectious diseases. The major barley diseasesprevalent in the world as well as in India include leafrust, covered and loose smut, spot or net blotch, powderymildew, stripe disease, bacterial blight and molya.Stripe disease caused by Drechslera graminea (Telomorph:Pyrenophora graminea) is an important seed borne diseaseof barley and responsible for 21.6% - 31.9% yield lossesin Rajasthan.